Pleckstrin homology domain leucine-rich repeat protein phosphatases set the amplitude of receptor tyrosine kinase output - Reyes, Gloria (National Academy of Sciences, 2014)
Growth factor receptor levels are aberrantly high in diverse cancers, driving the proliferation and survival of tumor cells. Understanding the molecular basis for this aberrant elevation has profound clinical implications. Here we show that the pleckstrin homology domain leucine-rich repeat protein phosphatase (PHLPP) suppresses receptor tyrosine kinase (RTK) signaling output by a previously unidentified epigenetic mechanism unrelated to its previously described function as the hydrophobic motif phosphatase for the protein kinase AKT, protein kinase C, and S6 kinase. Specifically, we show that nuclear-localized PHLPP suppresses histone phosphorylation and acetylation, in turn suppressing the transcription of diverse growth factor receptors, including the EGF receptor. These data uncover a much broader role for PHLPP in regulation of growth factor signaling beyond its direct inactivation of AKT: By suppressing RTK levels, PHLPP dampens the downstream signaling output of two major oncogenic pathways, the PI3 kinase/AKT and the Rat sarcoma (RAS)/ERK pathways. Our data are consistent with a model in which PHLPP modifies the histone code to control the transcription of RTKs.